HUBUNGAN MOTIVASI BELAJAR DENGAN PERILAKU BELAJAR MATA PELAJARAN EKONOMI SISWA SMA ISLAM HARUNIYAH PONTIANAK - Setiawati, Sulis; Warneri, Warneri; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of the research is the correlation of learning motivation with students learning behavior on the eleventh grade social major students in economics subject of SMA Islam Haruniyah Pontianak. The aim of the research is to find out the relationship between learning motivation and student’s learning behavior to the grade of XI social studies in economics subject of SMA Islam Haruniyah Pontianak. The research methodology used was descriptive research in the form of quantitative research. The sample of this research was the students of XI Social and the data was from the student’s answer of the questionnaire. The result of this research showed that learning motivation with the percentage of passion and desire 51,08%, motivation and needs in learning 55,47%, the prospect of student 44,92%, interesting activity 55,07% and learning environment 52,08%, it was in the category of less good. Student’s learning behavior in the XI Social studies Class with the percentage of habbit 54,68%, skill 41,14%, observation 47,41%, critical thinking and rational 48,43%, and attitude 54,69%, it was in the level of less good. The relationship between learning motivation and student’s learning behavior to the XI Social class in economics subject with the score of ttest 5,876 and the ttable is 2,000 with the 5% significant, which means ttest > ttable (5,876 > 2,000), it showed that Ha was accepted. The significant correlation between these 2 variables to the XI Social class in the economics subject of SMA Islam Haruniyah is 0,518, in the category of strong enough.Keywords:Learning Motivation, Learning Behavior, Students of XI Social Class, Economics Subject